Game Edukasi pada Mata Pelajaran Dasar Listrik dan Elektronika Berbasis Android - Muhammad Badruzzaman; Didik Aribowo Aribowo; Desmira Desmira (Program Studi Teknik Elektro Universitas Khairun, 2020)
Motivation for studetns in learning is due to the lack of attractive interactive learning media that makes students easy to underatand the material in class so that students have difficulty understanding the material presented by the teacher. The purpose of the study is to develop educational games as media on basic subjects of electricity and electronics and proxy tests on learning media based on student responses. The subjects of this study is an X class of electrical engineering at SMK public school of 4 serang cities of 21 people as responders. Research and development (RD) and use the waterfall model as a stage for developing the software. The development model consists of 5 stages, whoch are (1) analyses and rems, (2) system design and software, (3) implementation and testing of units, (4) integration and testing of system, (5) operations and maintenance. Studies show that an average value of 48,8 from student responses. Where as the results of the material worthiness show an average value of 51,7 with a range of scores x â‰¥ 45 â€œmost appropriateâ€, 45 x â‰¥ 37,5 â€œappropriateâ€ and x 30 â€œnot appropriateâ€. Based on the research that has been done, it can be concluded that android based educational games are based on basic subjects of electricity and electronics can be made into interactive learning media in the classroom with the â€œMost Appropriateâ€ category of student responses as well as material tests and media